ANALISIS JARINGAN LISTRIK 20 KV BERDASARKAN NILAI SAIDI-SAIFI TERHADAP PEMASANGAN TABUNG URGENT CUT OUT DI PT. PLN (PERSERO) ULP BINJAI TIMUR - Saragih, Naya Sari; Siagian, Parlin; Fahreza, Muhammad (Politeknik Harapan Bersama Tegal, 2024)
PT PLN (Persero) is a state electricity company that plays a crucial role in the distribution of electricity for the needs of the community, including supporting transportation activities, electronic devices at home/office/school/hospital, and, of course, electricity for a better life. In the current era, the challenges and demands for service and the reliability of electricity supply from customers are very high. In such conditions, the speed of handling during power disturbances becomes a benchmark, so both preventive and corrective work needs to be improved to maintain the reliability of the electricity supply, considering the values of SAIDI-SAIFI, Recovery Time, and ENS in electrical disturbances. In the distribution of electrical energy to consumers, there is a protective device called FCO (Fuse Cut Out). According to SPLN 64:1985 and SPLN D3.026:2017, FCO is a protective device that operates when there is an excess current disturbance. This device will disconnect one electrical circuit from another when the current passing through exceeds its working capacity. The working principle of FCO is to melt the fuse link inside the FCO tube, causing the FCO to detach. FCO is installed in the 20 kV distribution network, serving as protection for distribution transformers and network protection at branching points.